2015
DOI: 10.1111/acps.12440
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural changes in schizoaffective disorder compared to schizophrenia and bipolar disorder

Abstract: ObjectiveBrain structural changes in schizoaffective disorder, and how far they resemble those seen in schizophrenia and bipolar disorder, have only been studied to a limited extent.MethodForty‐five patients meeting DSM‐IV and RDC criteria for schizoaffective disorder, groups of patients with 45 matched schizophrenia and bipolar disorder, and 45 matched healthy controls were examined using voxel‐based morphometry (VBM).ResultsAnalyses comparing each patient group with the healthy control subjects found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
47
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 51 publications
8
47
1
Order By: Relevance
“…[9][10][11][12] Similarities between the cognitive profiles of these disorders are consistent with a shared under lying neurobiology that differs quantitatively rather than qualitatively across the diagnostic groups. 1,7,8 Indeed, previ ous studies have indicated overlap in regions of greymatter reduction (although less consistently in bipolar disorder) [35][36][37][38] and genetic susceptibility. [39][40][41][42] While neurocognitive impairments were evident across all diagnoses, impairments in social cognition were not present in bipolar disorder but were observed in schizophrenia and schizoaffective disorder.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Similarities between the cognitive profiles of these disorders are consistent with a shared under lying neurobiology that differs quantitatively rather than qualitatively across the diagnostic groups. 1,7,8 Indeed, previ ous studies have indicated overlap in regions of greymatter reduction (although less consistently in bipolar disorder) [35][36][37][38] and genetic susceptibility. [39][40][41][42] While neurocognitive impairments were evident across all diagnoses, impairments in social cognition were not present in bipolar disorder but were observed in schizophrenia and schizoaffective disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies found in SCZ patients GM reductions at the level of cerebellum (Molina et al 2011;Ivleva et al 2013;Amann et al 2016) Given the key function of these structures in learning, memory, attention and information transmission, the GM deficits of these structures in SCZ patients seem to be consistent with the relevant cognitive impairment associated with SCZ (Andreasen et al 1994;Brambilla et al 2013).…”
mentioning
confidence: 96%
“…In these studies, SCZ and BD were compared between each other and to HC, as well as to schizoaffective disorder (SAD) patients in Ivleva et al (2012Ivleva et al ( , 2013; Amann et al (2016), and to their firstdegree relatives in Ivleva et al (2013). It is worth noticing that Yüksel et al (2012) included SAD patients in the SCZ group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2,3] Until now, researchers have not decided on the independence of this disorder, and SAD is often included in the spectrum of schizophrenic disorders; rarely, it is referred to as bipolar disorder. [3][4][5][6][7] According to some studies, an overlap between schizophrenia, SAD and bipolar affective disorder type I was observed at the evaluation of genetic and biological parameters. [1,8,9] However, there are a number of modern clinical, molecular-genetic, biochemical and histological studies confirming the validity of segregation of such a nosological unit as schizoaffective disorder.…”
Section: Introductionmentioning
confidence: 99%